Electronic Theses and Dissertations in Peru: A Twelve-Year Experience and Its connections to “LA REFERENCIA”, a Latin American Repository - Huaroto, Libio (2015)
In June 2004, University of San Marcos (UNMSM, Lima, Peru) launched the first portal providing access to electronic theses and dissertations in Peru using the Cybertesis platform. This initiative marked the beginning of open access theses repositories in the country. It was followed by other higher education and research institutions, both public and private. Four years later, the Peruvian Network for Digital Theses was established. It was officially closed in December 2014. In June 2010, Red CLARA launched LA REFERENCIA, a project funded by Banco Interamericano de Desarrollo (BID). Eight regional countries were part of this initiative: Argentina, Brazil, Chile, Colombia, Ecuador, Mexico, Peru and Venezuela. El Salvador joined it recently. The aim of the project was to design a strategy for and an agreed framework on interoperability and scientific production management for Latin America. As of today, country members have developed national networks, each with its respective national repository portal. Repositories contain three (3) basic types of collections: master’s theses and doctoral dissertations; journal articles; and research projects. Participant institutions in LA REFERFENCIA are SNRD (Argentina), IBICT (Brazil), RRAAE (Ecuador), COLCIENCIAS, MEN, RENATA (Colombia), CONICYT, (Chile), CBUES (El Salvador), CONACYT, CUDI (México), RENARE (Peru), and CENIT, REACCIUN (Venezuela). Two events furthering open access to scientific research have been of key importance in Peru in the last two years; the first being the enacting of statute 30035 and its Regulations, by which the National Repository for Open Access Science and Technology was created. According to this legislation, all projects funded with public money will be openly accessible. The second event was the implementation of ALICIA (http://alicia.concytec.gob.pe), the aforementioned National Repository for Open Access Science and Technology. ALICIA is made up of 33 repositories – 13 of them are theses and dissertation repositories; 20 are institutional ones. ALICIA contains 34,567 registration records: 9,297 of them correspond to master’s theses, and 1,906 to doctoral dissertations (ALICIA has an additional 25,270 professional theses submitted by students after completing their undergraduate studies in order to obtain a professional license granted by the Peruvian state). LA REFERENCIA offers access to 88,599 doctoral dissertations and 202,798 master’s theses. Peruvian repositories for electronic theses and dissertations use DSpace, and have adopted the DRIVE 2.0 norms. Some institutions, like Universidad Peruana de Ciencias Aplicadas (UPC) have implemented Altmetrics indicators, showing social network activities connected to contents in theses, dissertations and journal articles.